MRT letter: Extended depth from focus reconstruction method for stretch zone measurement in 15-5PH steel - De Oliveira Caltabiano, Pietro Carelli Reis [UNESP]; Santos Rosa, Paulo Henrique [UNESP]; De Campos, Kamila Amato [UNESP]; De Oliveira Hein, Luis Rogerio [UNESP] (Wiley-Blackwell, 2012)
The stretch zone width (SZW) data for 15-5PH steel CTOD specimens fractured at -150 degrees C to + 23 degrees C temperature were measured based on focused images and 3D maps obtained by extended depth-of-field reconstruction from light microscopy (LM) image stacks. This LM-based method, with a larger lateral resolution, seems to be as effective for quantitative analysis of SZW as scanning electron microscopy (SEM) or confocal scanning laser microscopy (CSLM), permitting to clearly identify stretch zone boundaries. Despite the worst sharpness of focused images, a robust linear correlation was established to fracture toughness (KC) and SZW data for the 15-5PH steel tested specimens, measured at their center region. The method is an alternative to evaluate the boundaries of stretched zones, at a lower cost of implementation and training, since topographic data from elevation maps can be associated with reconstructed image, which summarizes the original contrast and brightness information. Finally, the extended depth-of-field method is presented here as a valuable tool for failure analysis, as a cheaper alternative to investigate rough surfaces or fracture, compared to scanning electron or confocal light microscopes. Microsc. Res. Tech. 75:11551158, 2012. (C) 2012 Wiley Periodicals, Inc.
Keywords: stretch zone size; 3D reconstruction; light microscopy; quantitative fractography